Answer :

(i) AB = {2, 3, 4, 5, 6, 7, 8}


(AB)’ = {1, 9}


A’ = {1, 3, 5, 7, 9}


B’ = {1, 4, 6, 8, 9}


A’B’ = {1, 9}


(AB)’ = A’B’


Hence proved


(ii) AB = {2}


(AB)’ = {1, 3, 4, 5, 6, 7, 8, 9}


A’B’ = {1, 3, 4, 5, 6, 7, 8, 9}


(AB)’ = A’UB’


Hence proved


These are also known as De Morgan’s theorem


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Mark the correct RD Sharma - Mathematics

Mark the correct RD Sharma - Mathematics

If A and B are twRD Sharma - Mathematics

If A and B are twRD Sharma - Mathematics

A survey shows thRD Sharma - Mathematics

If A = {x : x <spRS Aggarwal - Mathematics

Mark the correct RD Sharma - Mathematics

In a group of 70 RD Sharma - Mathematics

If P and Q are twRD Sharma - Mathematics